2012
DOI: 10.1212/wnl.0b013e31825dcdd9
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, randomized, controlled study of botulinum toxin type A in MS-related tremor

Abstract: This study provides Class III evidence that targeted injection of botulinum toxin type A is associated with significant improvement in MS-related upper limb tremor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 30 publications
0
55
0
Order By: Relevance
“…Small case series or single cases showed improvement after carbamazepine [116], propranolol, topiramate [117], primidone [118], isoniazid, ondansetron, or 4-aminopyridine [119], but there is insufficient evidence to support or refute efficacy of these drugs. A recent randomized, placebo-controlled, cross-over study [120] assessed botulinum toxin for MS-related limb tremor in 23 patients. Differences in all primary outcomes were highly significant at 6 and 12 weeks.…”
Section: Treatment Of Cerebellar Tremor Related To Msmentioning
confidence: 99%
“…Small case series or single cases showed improvement after carbamazepine [116], propranolol, topiramate [117], primidone [118], isoniazid, ondansetron, or 4-aminopyridine [119], but there is insufficient evidence to support or refute efficacy of these drugs. A recent randomized, placebo-controlled, cross-over study [120] assessed botulinum toxin for MS-related limb tremor in 23 patients. Differences in all primary outcomes were highly significant at 6 and 12 weeks.…”
Section: Treatment Of Cerebellar Tremor Related To Msmentioning
confidence: 99%
“…[3][4][5] We recently demonstrated that targeted onabotulinumtoxin A, a drug commonly used for focal dystonia, 6 reduces upper limb tremor severity in MS patients. 1,7 This finding, together with empiric clinical observation, raises the possibility that dystonia contributes to tremor in MS.The purpose of this study was to investigate the presence of upper limb dystonia and its contribution to tremor occurrence and severity in MS. We therefore recorded the presence and severity of dystonia in well-matched MS patients with and without tremor. …”
mentioning
confidence: 98%
“…However, studies of the effect of BT on other upper limb tremor types have had heterogeneous results in terms of functional disability. Although a placebo-controlled trial in multiple sclerosis-associated tremor1 and a case report in anti-MAG neuropathy-related tremor2 described significant improvement of both tremor and function, other studies of BT in essential or parkinsonian tremor failed to demonstrate functional improvement3,4 and/or to show change in objective tremor measures 5…”
Section: Discussionmentioning
confidence: 99%
“…In this context, use of botulinum toxin (BT) injections has had mixed results. Some studies have described significant improvement of both tremor and function,1,2 but others have failed to confirm those benefits 35…”
Section: Introductionmentioning
confidence: 99%